Sympathetic overactivation and catecholamine toxicity: mechanisms and therapeutic strategies for neurogenic heart injury following acute ischemic stroke - Guo, Wang; Li, Hong-yu; Li, Hong-xin; Nie, Qi-wen; Wang, Zhi-hao; Li, Jian-hui; Tang, Qiang (Frontiers in Cardiovascular Medicine, 2025)
Acute ischemic stroke (AIS) may trigger a spectrum of cardiac complications spanning arrhythmias, troponin elevation, Takotsubo cardiomyopathy, heart failure, and myocardial fibrosis and other acute or chronic cardiac lesions. These complications seriously affect the prognosis of patients. Existing studies have shown that the excessive excitation of the sympathetic neural network after cerebral ischemic injury leads to an increase in catecholamine levels, which may be a key factor triggering neurogenic cardiac damage after AIS. Therefore, evaluating the trigger areas of sympathetic nerve excitation and monitoring related cardiac damage indicators play a key role in patient management. Inhibiting excessive excitation of the sympathetic nerve, alleviating inflammatory responses and oxidative stress, is expected to become the core strategy for the prevention and treatment of neurogenic cardiac injury after AIS. Future research still needs to deeply explore the mechanism of cardiotoxicity mediated by the sympathetic neuro-catecholamine system after AIS, and at the same time promote clinical trials targeting the mechanism to verify treatment paradigms through translational models. This review aims to provide a useful reference direction for subsequent in-depth research.